Ovitrap surveillance of dengue vector mosquitoes in Bandung City, West Java Province, Indonesia - Sasmita, Hadian Iman; Neoh, Kok-Boon; Yusmalinar, Sri; Anggraeni, Tjandra; Chang, Niann-Tai; Bong, Lee-Jin; Putra, Ramadhani Eka; Sebayang, Amelia; Silalahi, Christina Natalina; Ahmad, Intan; Tu, Wu-Chun (PLOS Neglected Tropical Diseases, 2021)
Author summary The dengue virus, transmitted by Aedes vectors, has been continuously spreading in tropical and subtropical countries, causing illness and fatality. Given the lack of a cost-effective dengue vaccine, the vector control approach for reducing the Aedes population remains the key method for mitigating dengue transmission. For a successful vector control program, an effective vector surveillance system is crucial for precisely predicting the spatial and temporal risk of a dengue outbreak. The ovitrap system improves data collection efficiency, aiding long-term dengue vector monitoring activities. This study is one of the few long-term dengue vector surveillance programs in Indonesia and provides compelling evidence of the need to improve the existing conventional larval surveillance system. The results demonstrated that two dengue vector mosquitoes, A. aegypti and A. albopictus, were present in the study area, and A. aegypti was more prevalent than A. albopictus. We observed an interactive relationship between ovitrap placement and rainfall in the dynamics of ovitrap-related indices; understanding this relationship allows for timely initiation of vector control and intervention strategies. We conclude that the ovitrap surveillance system is a sensitive tool for monitoring the population dynamics of Aedes vectors, predicting dengue outbreaks, and potentially improving community-based conventional larval surveillance.